The Impact of Macroeconomic Policies on Foreign Direct Investment in Sudan (1990-2020) - Algzoli, Ebtihaj Hashim Mohammad (Journal of Economic, Administrative and Legal Sciences, 2024)
This study aimed to investigate the impact of macroeconomic policies on attracting foreign direct investment (FDI) in Sudan from 1990 to 2020 and its influence on the flow of FDI quantitatively, employing a standard model to estimate the FDI flow function during the specified period. The researcher adopted an analytical descriptive approach. One significant finding of the study was the presence of a notable correlation between the growth rate of gross domestic product (GDP), population size, economic openness, and FDI inflows during the study period. Additionally, the study revealed the positive impact of domestic financing and exchange rates on FDI. Exchange rates emerged as a crucial variable influencing FDI flows, underscoring their importance and positive role in fostering FDI in Sudan. Among the key recommendations, there is a necessity to enhance economic growth rates and incentivize foreign investors by establishing a conducive investment environment. Moreover, the country should strike a balance between monetary policies aimed at curbing inflation and efforts to attract foreign investments while addressing legislative, executive, and administrative barriers for foreign investors.